2017
DOI: 10.1063/1.4982941
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Inflection in the pressure dependent conductivity of the protic ionic liquid C8HIM NTf2

Abstract: Communication: Heterogeneous water dynamics on a clathrate hydrate lattice detected by multidimensional oxygen nuclear magnetic resonance

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…This is the first time an inflection in the pressure dependent Debye relaxation time was reported. These results are of high interest, since similar phenomena have been observed before in various dynamic properties and different materials [31][32][33][34][35] . Additionally, Lederle et al reported that an inflection in the temperature dependence of τ D at ambient pressure seems to be common behavior in simple MAs, and explained it with the reduction of supermolecular chain length upon heating 36 .…”
Section: Resultssupporting
confidence: 82%
“…This is the first time an inflection in the pressure dependent Debye relaxation time was reported. These results are of high interest, since similar phenomena have been observed before in various dynamic properties and different materials [31][32][33][34][35] . Additionally, Lederle et al reported that an inflection in the temperature dependence of τ D at ambient pressure seems to be common behavior in simple MAs, and explained it with the reduction of supermolecular chain length upon heating 36 .…”
Section: Resultssupporting
confidence: 82%
“…a transition from slower to faster than exponential pressure dependence in both properties. Similar observations were made before, both in PC and in other materials [25][26][27][28]. However, the presence of the inflection in the generated τ α isotherm is of special significance since no such feature can be observed in the reference isobar.…”
supporting
confidence: 86%
“…Fits of the viscosity data from Casalini and Bair according to eq result in p infl = p ( V act = min) ≈ 235 and 350 MPa for 298 and 328 K, respectively, in excellent agreement with our data. A linear p infl ( T ) dependence seems to be common behavior for materials without significant hydrogen bonding . A linear fit (line in Figure ) with a slope of 4.7 MPa/K adequately describes the data.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Macroscopic transport properties in ionic liquids are typically investigated by dielectric spectroscopy, 9 11 conductivity experiments, 12 14 or rheology, 15 and based on these length scales, a close correlation between viscous flow and ion transport has been inferred. 16 , 17 On microscopic-length scales, dynamics has been studied by, e.g., nuclear magnetic resonance, 18 , 19 quasi-elastic neutron scattering (QENS), 20 28 and molecular dynamics simulations.…”
Section: Introductionmentioning
confidence: 99%